A Detailed Study of Intrusion Detection in Data Mining - E. Kesavulu Reddy; V. Naveen Reddy; P. Govinda Rajulu (Research Issues on Datamining, 2021)
Network security technology has become crucial in protecting the computing infrastructure of the government and industry. Modern intrusion detection applications are confronted with a variety of issues. These applications must be reliable, extensible, manageable, and minimal in maintenance costs. Data mining-based intrusion detection systems (IDSs) have shown high accuracy, good generalisation to novel types of intrusion, and stable behaviour in a changing environment in recent years. Despite this, there are considerable obstacles in the design and deployment of high-quality IDSs. Data transformations, model deployment, cooperative distributed detection, and sophisticated engineering endeavours are examples of instrumenting components.